SOME ASPECTS CONCERNING THE UTILIZATION OF DIETARY NITROGEN FOR THE PRODUCTION OF MICROBIAL PROTEIN IN THE RUMEN - ΒΛΑΣΤΑΡΑΚΟΣ, Π. (Journal of the Hellenic Veterinary Medical Society, 1973)
A brief review on rumen microbiology is given. Dietary nitrogen given either as organic or inorganic form produces mainly ammonia in the rumen. Ruminai incorporation of ammonia into microbial protein allows for the production of high value protein. Microbial metabolism in the ruminants requires that the ruminants absorb a nutrient mixture, containing an excess of energy relative to protein. The continual presence of uria in the saliva keeps rumen ammonia at normal level and allows for the continual microbial proliferation for a long time after feeding.